Biodegradable Nanoparticles Containing Benzopsoralens: An Attractive Strategy for Modifying Vascular Function in Pathological Skin Disorders - Gomes, Anderson J.; Lunardi, Laurelucia O. [UNESP]; Caetano, Flávio Henrique [UNESP]; Machado, Antonio Eduardo H.; Oliveira-Campos, Ana Maria F.; Bendhack, Lusiane M.; Lunardi, Claure N. (Wiley-Blackwell, 2011)
Psoralens are often used to treat skin disorders such as psoriasis, vitiligo, and others. The toxicity and fast degradation of these drugs can be diminished by encapsulation in drug-delivery systems (DDS). Nanoparticles (NPs) containing the benzopsoralen (BP) (3-ethoxy carbonyl-2H-benzofuro[3,2-e]-1-benzopiran-2-one) were prepared by the solvent-evaporation technique, and parameters such as particle size, zeta potential, drug-encapsulation efficiency, and external morphology were evaluated. The analysis revealed that the NPs are spherical and with smooth external surface with diameter of 815 +/- 6 80 nm, they present low tendency toward aggregation, and the encapsulation efficiency was of 74%. The intracellular distribution of NPs as well as their uptake by tissues was monitored by using laser confocal microscopy and transmission electron microscopy (TEM). The use of a BP in association with ultraviolet light (360 nm) revealed by TEM morphological characteristics of cell damage such as cytosolic vesiculation, mitochondria condensation, and swelling of both the granular endoplasmic reticulum and the nuclear membrane. The primary target of DDS and drugs in vascular system are endothelial cells and an attractive strategy for modifying vascular function in various pathological states of skin disorders, cancer, and inflammation. The results presented in this work indicate that poly(lactic-co-glycolic acid) NP should be a promising sustained release for BP for systemic and local delivery associated with ultraviolet irradiation (PUVA therapy). (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 1348-1354, 2011
Keywords: nanoparticles; biological applications of polymers; drug-delivery system; microencapsulation; TEM